RELATIONSHIP OF POST-OPERATIVE INOTROPIC USE AND MORTALITY IN CABG PATIENTS WITH RADIAL GRAFTS - DAR , FN; YUNUS , A; NIAZ , MN (Biological and Clinical Sciences Research Journal, 2023)
This retrospective analysis aimed to assess the effect of post-operative use of inotropic support on the long-term mortality rates of coronary artery bypass graft (CABG) patients who had undergone radial grafts. Inotropic drugs are frequently administered to improve heart function after surgery, but their impact on long-term survival is still controversial. The primary objective was to compare the 10-year mortality rates between patients who received post-operative inotropic support (Group A) and those who did not (Group B). We also sought to determine whether inotropic infusion correlated with improved or worsened long-term survival. A total of 80 participants were retrospectively analyzed, with Group A consisting of 18 individuals who received inotropic support and Group B comprising 62 individuals without such support. Demographic and clinical characteristics, including age, gender, comorbidities, clinical parameters, ejection fraction, New York Heart Association (NYHA) functional class, and 10-year mortality rates, were assessed and compared between the two groups. Kaplan-Meier survival analysis was done to assess the survival benefits. The analysis revealed no significant difference in 10-year mortality rates between Group A and Group B, with an insignificant p-value of 0.987. The Kaplan-Meier survival analysis and log-rank test further supported this finding, indicating no significant relationship between the absence of inotropic infusion and increased survival chances. These results suggest that post-operative inotropic support may not significantly influence long-term survival. Inotropic infusion may not be necessary for improving or worsening 10-year survival rates in surgical patients. While this retrospective analysis provides valuable insights, further research, particularly larger prospective studies, and randomized controlled trials, is needed to validate these findings and offer more conclusive guidance regarding the use of inotropic agents in post-operative care.